2012
DOI: 10.3109/10903127.2012.670688
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Ambulance Use Among Patients with Low-Acuity Conditions

Abstract: Our study builds on a body of work highlighting the factors associated with ambulance transport to EDs, confirms that certain vulnerable populations disproportionately use ambulances, and may inform interventions aimed at increasing access to nonambulance transportation and urgent care for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 25 publications
2
66
2
Order By: Relevance
“…Most patients causing self-induced injury often have psychological diseases,16 and medical staff in non-psychiatric emergency departments might refuse the request from EMS personnel to receive such patients because of the difficulty in treating them. In addition, these patients tend to call for ambulances and frequently visit emergency departments,17–19 which might also affect the difficulty in hospital acceptance. Trauma by assault was also one of the predictors of the difficulty in hospital acceptance at the scene, and emergency hospitals would hesitate to receive patients with such injuries because there are not emergency hospitals for the emergency transport of these patients by law in Japan, and it is difficult for staff to continuously monitor them in hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients causing self-induced injury often have psychological diseases,16 and medical staff in non-psychiatric emergency departments might refuse the request from EMS personnel to receive such patients because of the difficulty in treating them. In addition, these patients tend to call for ambulances and frequently visit emergency departments,17–19 which might also affect the difficulty in hospital acceptance. Trauma by assault was also one of the predictors of the difficulty in hospital acceptance at the scene, and emergency hospitals would hesitate to receive patients with such injuries because there are not emergency hospitals for the emergency transport of these patients by law in Japan, and it is difficult for staff to continuously monitor them in hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with evidence of access barriers in the use of ambulance and ED services in the form of limited transport alternatives, health literacy, and English proficiency. 3945 In assessing the implications of differential ambulance use, we note that there is “no expert consensus on what constitutes medical necessity for ambulance use” and perception of emergent need may vary. 39,46 Evidence indicates that ambulance use is associated with improved patient outcomes, particularly for time-sensitive acute medical events, such as, stroke, 8 myocardial infarction, cardiac arrest 11 and respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…Given that much of the current evidence on ambulance use is based on NHAMCS data, which is a survey of ED patients, our findings indicate that the patterns on ambulance use obtained from NHAMCS data may not be representative of population-level patterns in use of ambulance. 5,7,39,44,47 …”
Section: Discussionmentioning
confidence: 99%
“…We found the superuser population was represented by a much higher proportion of Medicaid recipients that the average 2009 EMS population, which has important implications for state Medicaid agencies attempting to reduce expenditures. Previous studies have demonstrated that publicly insured individuals disproportionally use ambulance transport and ED services, 25,30 especially for low-acuity conditions 31 or alcohol-related disorders. 25 However, in many communities EMS personnel are left with no alternative transport destination apart from the ED.…”
Section: Discussionmentioning
confidence: 99%